Предмет: Алгебра, автор: pavelpetrovskiy

Упростите выражение: (√ x - √ y) (6√ + 6√ y) (3√x - 6√ xy + 3√ y)
Цифры перед корнями - это степень корня

Ответы

Автор ответа: Удачник66
0

Ответ:

x - y

Объяснение:

(\sqrt{x} -\sqrt{y} )(\sqrt[6]{x} +\sqrt[6]{y} )(\sqrt[3]{x}-\sqrt[6]{xy}+\sqrt[3]{y}  )=A

Сделаем замену \sqrt[6]{x} =a; \sqrt[6]{y} =b; \sqrt[3]{x} =a^2; \sqrt[6]{xy} =ab; \sqrt[3]{y} =b^2

A=(\sqrt{x} -\sqrt{y} )(a+b)(a^2-ab+b^2)=(\sqrt{x} -\sqrt{y} )(a^3+b^3)=A

Обратная замена: \sqrt[6]{x} =a; \sqrt[6]{y} =b; a^3=(\sqrt[6]{x})^3=\sqrt{x} ; b^3=(\sqrt[6]{y})^3=\sqrt{y}

A=(\sqrt{x} -\sqrt{y} )(\sqrt{x} +\sqrt{y} )=x-y

Похожие вопросы